O Teorema de Pitágoras: alternativas de demonstrações - Evangelista, Luís Antonio [UNESP] (2014)
This work aims to show that the Pythagorean Theorem, a major creations in mathematics, should not be seen as a simple formula to memorize, but as an important and useful tool that should be demonstrated. Because the statements are normally very little worked in elementary and high school, most students and teachers have no opportunity to meet the enormous wealth of their applications and the different statements often surprising. In addition to presenting this work six historic and classic statements, is also presented as alternative education, experimental activity to induce students to the Pythagorean theorem, as well as motivate them to meet their statements. Such activity was applied with students of the first year of high school and the results were positive, as can be seen here